Safety Training as a Predictor of Seafarers Performance - Nurahaju, Rini; Utami, Dessy Nur (Institut Teknologi Sepuluh Nopember, 2020)
A good performance of seafarers is expected by any shipping company because it will bring benefits to the company itself. In order to get this performance, seafarers as one of the important assets must be managed properly by the company. One of them is the participation of seafarers to attend training for mutual safety. The purpose of this study was to analyse the effect of training on seafarers' performance. The sample in this study amounted to 100 seafarers who happened to be attending education in educational institution, which were selected using incidental sampling techniques. Research uses a training scale and a performance scale to measure seafarers' perceptions of training that has been conducted and performance as a result. Data were analysed using a simple regression test. Regression test results show that training has a positive and significant role on the performance of seafarers.Â Â